Abstracts of the 16th European Conference on Eye Movements 2011 - Françoise Vitu; Eric Castet; Laurent Goffart (Bern Open Publishing, 2001)
This document contains all abstracts of the 16th European Conference on Eye Movements, August 21-25 2011 in Marseille, France. It was a real honour and a great pleasure to welcome more than 500 delegates to Marseille for the 16th edition of the European Conference on Eye Movements. The series of ECEM conferences started in 1981 under the auspices of Rudolf Groner in Bern. This year, we therefore celebrated the 30th Anniversary of ECEM. For this special occasion we had as a special guest Rudolf Groner, and honoured Alan Kennedy and George W. McConkie for their contributions to our field in two special symposia. We had the pleasure of listening to six keynote lectures given respectively by Patrick Cavanagh, Ralf Engbert, Edward L. Keller, Eileen Kowler, Rich Krauzlis and Gordon E. Legge. These exceptional scientific events were nicely complemented by all submissions, which made the ECEM 2011 program a very rich and interdisciplinary endeavor, comprising 19 symposia, 243 talks and 287 poster presentations, and a total of about 550 participants. The conference opened with an address given by Denis Bertin, vice president of the scientific committee of the University of Provence, and representing Jean-Paul Caverni, President of the University of Provence. It closed with Rudolf Groner's address and the awarding of the best poster contributions by students and postdocs. This year, three posters were awarded; the first prize was offered by SR Research, the second prize was given by the Cognitive Science Society, and the third, the Rudolf Groner Prize, was offered by the ECEM organizing committee. The conference was held on the St Charles campus of the University of Provence, and to mark the return of ECEM in Southern Europe, many events including lunches, coffee breaks, aperitifs and poster sessions took place outside under the trees of our campus. Luckily, the sun was with us for the five days of the conference ! Françoise, Stéphanie, Stéphane, Eric & Laurent